Feasibility of a structured group education session to improve self-management of blood pressure in people with chronic kidney disease: an open randomised pilot trial. Issue 2 (19th December 2011) - Byrne, Jo; Khunti, Kamlesh; Stone, Margaret; Farooqi, Azhar; Carr, Sue
Abstract : Objectives: We aimed to test, at pilot level, a structured group educational intervention to improve self-management of blood pressure in people with chronic kidney disease (CKD). The current paper explores patient acceptability of the intervention. Design: This was an open randomised pilot trial. Participants were randomly assigned to either: A control group (n=41) receiving standard clinical management of hypertension. An intervention group (n=40) receiving standard clinical care plus the educational intervention. Setting: Renal outpatient clinics at a single study centre. Participants: Patients with early CKD and hypertension were identified and approached for recruitment. Intervention: An evidence-based structured group educational intervention (CHEERS) using the principles of social cognitive theory to improve knowledge and self-management skills. Outcomes: Recruitment, uptake of the intervention and patient satisfaction were evaluated to explore patient acceptability of the intervention and to determine any differences between patients regarding recruitment and retention. Measures: Data on age, sex and ethnicity were collected for all patients approached to take part. For recruited patients, data were also collected on self-efficacy (ability to self-manage). Reasons given by patients declining to take part were recorded. Patients attending the educational session also completed an evaluation form to assess satisfaction. Results: A total of 267 patients were approached, and 30% were randomly assigned. Lack of time (48%) and lack of interest (44%) were the main reasons cited for non-participation in the study. Men were significantly more likely to be recruited (p=0.048). The intervention was rated enjoyable and useful by 100% of participants. However, 37.5% of the intervention group failed to attend the educational session after recruitment. Participants failing to attend were significantly more likely to be older (p=0.039) and have lower self-efficacy (p=0.034). Conclusion: The findings suggest that delivering and evaluating an effective structured group educational intervention to promote better blood pressure control in patients with CKD would be challenging in the current context of kidney care.